CVD Polymers for Devices and Device Fabrication. Issue 11 (29th December 2016) - Wang, Minghui; Wang, Xiaoxue; Moni, Priya; Liu, Andong; Kim, Do Han; Jo, Won Jun; Sojoudi, Hossein; Gleason, Karen K.
Abstract : Chemical vapor deposition (CVD) polymerization directly synthesizes organic thin films on a substrate from vapor phase reactants. Dielectric, semiconducting, electrically conducting, and ionically conducting CVD polymers have all been readily integrated into devices. The absence of solvent in the CVD process enables the growth of high‐purity layers and avoids the potential of dewetting phenomena, which lead to pinhole defects. By limiting contaminants and defects, ultrathin (<10 nm) CVD polymeric device layers have been fabricated in multiple laboratories. The CVD method is particularly suitable for synthesizing insoluble conductive polymers, layers with high densities of organic functional groups, and robust crosslinked networks. Additionally, CVD polymers are prized for the ability to conformally cover rough surfaces, like those of paper and textile substrates, as well as the complex geometries of micro‐ and nanostructured devices. By employing low processing temperatures, CVD polymerization avoids damaging substrates and underlying device layers. This report discusses the mechanisms of the major CVD polymerization techniques and the recent progress of their applications in devices and device fabrication, with emphasis on initiated CVD (iCVD) and oxidative CVD (oCVD) polymerization. Abstract : Chemical vapor deposition (CVD) polymerization synthesizes conformal and pinhole‐free organic thin films directly on substrates. Compared with solution‐based techniques, the solvent‐free nature of the CVD process avoids the undesirable monomer–solvent or polymer–solvent and solvent–substrate interactions. Thus, CVD is particularly suitable for synthesizing insoluble conductive polymers and robust crosslinked networks for organic devices.